ARENARIA Dl VAL SABBIA E FORMAZIONE Dl GORNO: UN SISTEMA DEPOSIZIONALE DELTA-LAGUNA NEL TRIAS SUPERIORE DELLE PREALPI BERGAMASCHE (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
A deltaic—lagoonal depositional system has been identified in the Triassic of the Bergamasc Alps (Lombardy, northern Italy). The following sedimentary environments have been distinguished:A) subaerial delta Plain (reddish sandstones and siltstones organized in fining—upward sequences); B) Iower delta Plain / delta front / proximal prodelta (greenish sandstones and siltstones, locally organized in fining—upward sequences) ;BI) near—shore lagoonal areas situated far from the "entry—points" of the sands (alternating dark grey limestones — often oolitic grainstones and dark grey mudrocks, with some greenish sandstones and grey hybrid arenitesC) distal prodelta (alternating dark grey mudrocks, dark grey limestones and greenish sandstones); D) central part of the lagoon (dark grey limestones and marls; locally dark grey mudrocks).
Keywords: Deltaic and lagoonal deposits; Triassic.